A first high-resolution carbon isotope stratigraphy from the Boreal (NW Germany) for the Berriasian to Coniacian interval—implications for the timing of the Aptian–Albian boundary - Bornemann, André; Erbacher, Jochen; Blumenberg, Martin; Voigt, Silke (Frontiers in Earth Science, 2023)
High-amplitude changes in sedimentary δ13C characterize the Cretaceous system and have been proven useful for supra-regional chemostratigraphic correlation. In the Cretaceous, these δ13C perturbations indicate large shifts between the global carbon reservoirs that are usually caused by volcanic activity of large igneous provinces, the widespread deposition of thick organic carbon-rich sequences and/or changes in orbital parameters. Here, we present an upper Berriasian to lower Coniacian (c. 142–88 Ma) composite carbon isotope record based on 14 drill cores, 2 outcrops, and almost 5,000 samples. The total record comprises a composite thickness of more than 1,500 m. All cores and successions are located in the larger Hanover area, which represents the depocenter of the North German Lower Saxony Basin in Early to mid-Cretaceous times. In Northern Germany, Boreal Lower Cretaceous sediments are predominantly represented by CaCO3-poor mud and siltstones of up to 2,000 m thickness, which become more carbonate-rich during the Albian–Cenomanian transition and even chalkier in the upper Cenomanian to Coniacian interval. The carbon isotope record reveals a number of global key events, including the Valanginian Weissert Event, the Oceanic Anoxic Events (OAEs) 1a and d, and the Kilian Event (Aptian–Albian boundary, part of OAE 1b). For the early Late Cretaceous, the Mid-Cenomanian Event, the OAE 2 (Cenomanian–Turonian Boundary Event), and the Navigation Event, among others, have been identified. The Kilian Event represents the Aptian–Albian boundary and has been identified herein for the first time in Northern Europe. Based on the evaluation of its relative position to the Vöhrum boundary tuff, we tentatively propose a slightly older age for the Aptian–Albian boundary of c. 113.65 Ma instead of 113.2 Ma. The observed chemostratigraphic events enable a detailed stratigraphic comparison with Tethyan and other Boreal records and associated paleoenvironmental data. Thus, this new detailed chemostratigraphy provides a unique opportunity to potentially overcome many still existing Boreal–Tethyan correlation issues. The presented record can be considered almost complete, albeit a 2-Myr gap during the early Albian is likely, and condensed intervals occur specifically during the lower Aptian.